Modelling of the film thickness effecton the carrier's mobility in polysilicon thin film transistors - Bourezig, Y.; Bouabdallah, B.; Mansouri, S.; Gaffiot, F. (Universiti Malaysia Perlis, 2009)
Link to publisher's homepage at http://www.unimap.edu.my/ ; Open access only applicable for vol. 1; issue 1, 2008 & vol. 2; issue 1, 2009.